2015
DOI: 10.1111/ajco.12419
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor activity of pro‐apoptotic agent PAC‐1 with cisplatinum by the activation of CASP3 in pulmonary adenocarcinoma cell line H1299

Abstract: Aim: Evasion of apoptosis is a hallmark of human cancer cells. We sought to explore the potential synergistic antitumor activity and underlying mechanisms of the pro-apoptotic agent PAC-1 plus cisplatinum (Cis) in non-small cell lung cancer (NSCLC) cell lines. Methods: The adenocarcinoma cell lines H1299, A549, PC9, H1650 and H1975 were used as in vitro models. Colorimetric MTT assays, Western blotting and flow cytometry were used to evaluate the antigrowth effects of PAC-1 and/or Cis and apoptosis status. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…10 fold in H1299 cells and 3 fold in P31 cells when compared to the parental cells. These data are consistent with data for cisplatin sensitivity reported for H1299 cells by Johansson et al [ 15 ] and Huang et al [ 21 ], for H1299r cells [ 15 ] and for P31 and P31r cells reported by Janson et al [ 22 ] and Johansson et al [ 15 ]. In addition, we observed that there was a significantly greater proliferation rate in the sensitive cell lines when compared to the resistant cell lines for both H1299 and P31 cells, an observation consistent with that measured previously for these cells by Tyler et al [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…10 fold in H1299 cells and 3 fold in P31 cells when compared to the parental cells. These data are consistent with data for cisplatin sensitivity reported for H1299 cells by Johansson et al [ 15 ] and Huang et al [ 21 ], for H1299r cells [ 15 ] and for P31 and P31r cells reported by Janson et al [ 22 ] and Johansson et al [ 15 ]. In addition, we observed that there was a significantly greater proliferation rate in the sensitive cell lines when compared to the resistant cell lines for both H1299 and P31 cells, an observation consistent with that measured previously for these cells by Tyler et al [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…S1A–C). Collectively these results demonstrate that, in addition to general cytotoxins and inhibitors against BRAF V600E (Botham et al, 2016; Huang et al, 2016; Peh et al, 2016; Razi et al, 2015), PAC-1 is able to broadly enhance the caspase-3 activity of kinase inhibitors targeted to EGFR T790M , EML4-ALK, and BCR-ABL.…”
Section: Resultsmentioning
confidence: 73%
“…Given that NSCLC has not been associated with genetic alterations directly affecting H3K27 methylation, our finding may provide a rationale to encourage exploration of the potential of GSKJ4 as an anticancer agent against a wider range of cancers than previously thought. The NSCLC cell lines used in this study were A549 (poorly differentiated adenocarcinoma with mutated KRAS, wild-type (wt) TP53 and wt EGFR), H1299 (poorly differentiated adenocarcinoma with wt KRAS, homozygous deletion of TP53 and wt EGFR) and PC9 (well differentiated adenocarcinoma with wt KRAS, wt TP53 and mutated EGFR) (32)(33)(34)(35)(36)(37)(38). Although A549 appeared to be somewhat more sensitive than the other two, GSKJ4 quite effectively inhibited the growth of all three cell lines at 2 μM, a concentration that did not affect the growth of normal human fibroblasts, which may imply that GSKJ4 exerts its anticancer effect irrespective of the genetic status of the KRAS, TP53 and EGFR genes.…”
Section: Discussionmentioning
confidence: 99%